Diagnosis and management of erectile dysfunction. Issue 5 (23rd September 2021) - Bromby, Adam; Modgil, Vaibhav; Pearce, Ian
Abstract : Erectile dysfunction is common and may signal vascular disease, so a cardiovascular risk assessment is important for these patients. Thorough counselling is needed along with discussion of all treatment options at an early stage to facilitate shared decision making.